MENINGKATKAN HASIL BELAJAR PASSING ATAS BOLA VOLI MELALUI PERMAINAN 3 ON 3 PADA SISWA SEKOLAH MENENGAH PERTAMA - Nulhadi, Agus; Ashari, L Hasan; Herlina, Herlina; Burhan, Zakir (LPPM Institut Pendidikan Nusantara Global, 2023)
Education in Indonesia requires special attention, because many educators who have plunged into the world of teaching but do not have certification. This will certainly have an impact on the quality of learning carried out, because educator certification itself aims to be able to improve the professionalism of an educator. The research method used is descriptive qualitative, where the instruments used are interviews and observations conducted at SDN Lialang with one of the teacher in class IV, things that will be studied more deeply about how the relationship between the implementation of teacher competencies as part of the role and duties of educators with the background of non-certified educators. Educators who do not have four competencies make them unprofessional educators, this is indicated by not being able to make learning tools, not understanding the material fully, using media and models that are not adjusted, not reflecting and evaluating, lack of understanding of students, unstable emotional maturity of educators, and rarely communicating with parents of student.